2017
DOI: 10.2134/jeq2017.05.0180
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Column Evaluation of High Explosives Attenuation in Grenade Range Soils

Abstract: High explosives (HEs) deposited on military ranges can leach through the soil and contaminate groundwater. We examined the transport and fate of HEs in laboratory columns containing soils from two hand grenade bays (Bays C and T) and the impact of organic amendments on biodegradation. Soil characteristics were similar; however, Bay C had somewhat higher clay and organic C. Experimental treatments included addition of crude glycerin and lignosulfonate, and parallel control columns. Experimental results showed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Similar results were observed by Won and Borden (2017) in laboratory column experiments with Bay T soil. Six to twelve months after GL+LS addition, small amounts of TOC and Cl were discharged in the column effluent, followed by a rapid decline in NO 3 , and increase in Mn, and removal of RDX.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were observed by Won and Borden (2017) in laboratory column experiments with Bay T soil. Six to twelve months after GL+LS addition, small amounts of TOC and Cl were discharged in the column effluent, followed by a rapid decline in NO 3 , and increase in Mn, and removal of RDX.…”
Section: Discussionsupporting
confidence: 89%
“…However, nitrate and RDX levels recovered much more slowly due to the low drainage rates and long travel time through the soil. Similar results were observed in laboratory column experiments containing Bay C soil, where saturated, anoxic conditions reduced RDX leaching by 92% (Won and Borden, 2017). Larson et al (2008) observed similar results at Fort Jackson, SC, where RDX levels varied from <1 to 3200 μg L −1 (average = 435 μg L −1 ) in suction lysimeters installed below an untreated grenade bay.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These experiments can be classified into static, in which the outcome does not change over time, and dynamic, in which the outcome changes over time (UK Government Office for Science, 2018). Static experiments, such as bottle flask tests and microcosms have been performed to study processes affecting persistence such as the degradation rate of explosives and reversible and irreversible sorption onto soil (Halasz et al, 2018;Indest et al, 2017;Krzmarzick et al, 2015;Won and Borden, 2017). In this way, key parameters for defining transport processes such as partition coefficients (matrix-water, organic carbon-water, octanol-water etc…) and half-life times of IHE in different media have been quantified.…”
Section: Introductionmentioning
confidence: 99%